The Influence of shales characteristics on CO2 adsorption behaviour under sub-critical conditions - Al-Mutarreb, A.M. (Institute of Physics Publishing, 2018)
Shale gas has been an important source of natural gas and is expected to contribute 30 towards the global output by 2040. Shale formations also have CO2 sequestration potential, which could be used to mitigate the greenhouse gas emissions. A quarter of Malaysian's sedimentary comprises of black shale formations. In this article, we evaluated the CO2 sequestration potential of some of Malaysian's formation under sub-critical conditions, and we correlate shale's characteristics to CO2 storage behaviour under sub-critical conditions. The evaluation is based on total organic carbon (TOC wt. ) contents, mineralogical compositions, particle size distribution PSD of mesopores and micropores. The results show that total organic carbon measured by TOC analyser ranges between 0.5wt. to 12.1wt. Bulk mineralogical composition was semi-quantified using X-ray Diffraction (XRD). Non-clay composition varies between â¼35 wt. to â¼75 wt. , which is dominated by quartz. All samples also contain clay minerals such as kaolinite and illite at different range. The CO2 adsorption isotherm results show that KH sample adsorb the most while in contrast the KL samples adsorb the least of CO2. Positive correlation between organic content and CO2 adsorption was observed in most samples, indicating that formations with high organic content has higher CO2 sequestration potential. Mineralogical composition also influence the CO2 adsorption, for instance, illite has lower surface area and pore volume compare with some other clays, subsequently, its presence reduced the CO2 storage potential on KL sample. However, the application of this observation may not fit to other formations due to the high degree of heterogeneity of shale formations. Â© Published under licence by IOP Publishing Ltd.